Optimal Web Service Selection Model using Fuzzy Extended AHP and Weighted Sum Method- - Rachna Kohar (Journal of Digital Information Management, 2018)
Different services have different values for their different properties (functional and non-functional). Moreover, consumers have different preferences for these properties. Since these preferences may be incomplete/ vague/imprecise, this inevitably can in turn cause selection of a non-optimal service for the consumer which may not have the desired value for these properties for the consumer. Therefore optimal web service selection based on the consumer’s preferences is a challenging task. In this paper, a new service selection model is proposed which considers consumer preferences for different service properties as well as the actual values of its properties. Services are evaluated and priority weights are computed separately for functional and non-functional properties using modified Fuzzy Extended Analytic Hierarchy Process (FEAHP) and Weighted Sum Method (WSM) respectively. Real time data is used to conduct experiments.